The ABILITY OF SARS-CAPABLE COV-2S - Manjot Kaur, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The SARS-CoV-2 coronavirus outbreak has had a significant impact on the health and economics of people all around the world, but especially in the United States. The SARS-CoV-2 virus is to blame for this year's coronavirus outbreak, which is very dangerous and rapidly expanding (COVID-19). Researchers have demonstrated that SARS-CoV-2 may infect a wide spectrum of animals in the lab as well as in the wild. Unlike other species, such as hamsters, white-tailed elk, deer mice, and non-human primates, domestic cats and big cats are susceptible to the virus. Few studies have examined whether SARS-capable CoV-2s may spread to domestic sheep (Ovis aries), a typical household ruminant.